Supporting Clients Who Experience Anxiety About COVID-19 - Jack, Ellie M. (Canadian Journal of Counselling and Psychotherapy, 2020)
In this composite case study, a client sought counselling to manage her anxiety about COVID-19. Theoretical approaches used included psychoeducation, narrative therapy, and cognitive behavioural therapy. These therapeutic methods helped the client experience a reduction in anxious thoughts and emotions concerning COVID-19.